Spatial analysis of competition among local governments and the price of land: the case of Zhejiang Province. Issue 3 (2nd July 2016) - Kajitani, Kai; Fujii, Daisuke
Abstract: This empirical study focuses on competition between local governments as they strive to attract companies through the auction of land use rights. In the literature on competition between local governments, the focus has tended to be toward growth rates based on performance evaluation or tax rate-based competition for attracting companies. In China, the property tax system is still underdeveloped and local governments cannot independently set tax rates. Therefore, this study focuses on a type of 'dumping' activity by which local governments auction land use rights to attract industrial companies and empirically test this hypothesis using the spatial lag model.